(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article analyzes the role of artificial intelligence in the educational system and its influence on diplomacy, the issue of increasing the influence of intelligence. The introduction of artificial intelligence into the teaching process at universities, as well as the need to improve Internet technologies, was determined. Opportunities to use artificial intelligence to improve the quality of education are presented. Attention is paid to the need to use and improve neural networks and artificial intelligence technologies in the educational system.